Pentingnya Sumberdaya Alam bagi Masyarakat Lokal di Daerah Aliran Sungai Mamberamo, Papua, dan Implikasinya bagi Konservasi - Manuel Boissiere; Miriam van Heist; Douglas Sheil; Imam Basuki; Scott Frazier; Untung Ginting; Meilinda Wan; Bambang Hariadi; Hendri Hariyadi; Hari Dwi Kristianto; Jance Bemei; Rafles Haruway; Eddy R. Ch. Marien; Denis Piet H. Koibur; Yoseph Watopa; Ismail Rachman; Nining Liswanti (The Ethnobiological Society of Indonesia, 2004)
Sparsely populated and abundant in rich and exotic bio-diversity, the vast and highly inaccessible Marnberamo Basin in Indonesia's West Papua (Irian Jaya) contains some of the world's most pristine rainforests. The region's 7,000 people and their communities are spread over 7.7 million hectares of low-swamps, vast forests and high mountains, and maintain considerable wariness towards outsiders. This article concerns the villagers of one such community, focusing on how they perceive and prioritize their natural resources, landscape and the conservation of the surrounding floodp]ain and watershed. What are the perceptions of the villagers regarding their natural environment? What is important for them? What are the implications for conservation? This account illustrates some of the considerable information on the landscape and its resources, the main threats facing biodiversity, and local livelihoods gathered during our study. Among the many outputs and results, the most striking to us was the knowledge it provides on how building strong local trust is vital to increasing the awareness of and support for conservation among remote communities.